2021
DOI: 10.1002/cam4.3761
|View full text |Cite
|
Sign up to set email alerts
|

The optimal cut‐off value in fit‐based colorectal cancer screening: An observational study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Unexpectedly, we found no statistically significant difference in CRC incidence between men and women. Numerous studies have suggested that the FIT is more sensitive in men than in women, as women more often have right-sided cancer, which tends to bleed less 16 17 18 . Therefore, we would have expected the number of cancers in the FIT-negative group to be higher in women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, we found no statistically significant difference in CRC incidence between men and women. Numerous studies have suggested that the FIT is more sensitive in men than in women, as women more often have right-sided cancer, which tends to bleed less 16 17 18 . Therefore, we would have expected the number of cancers in the FIT-negative group to be higher in women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…A positive test triggers a recommendation for conventional colonoscopy. False positive FIT tests relate to stool concentration, with sensitivity increasing and specificity decreasing with higher cut-off levels [ 77 ]. The test cannot distinguish bleeding arising from advanced neoplasia or from non-neoplastic disorders, including peptic ulceration, inflammatory bowel, and hematological diseases [ 78 ].…”
Section: The Role Of Colon Capsule Endoscopy In Screening For Advance...mentioning
confidence: 99%
“…In attempts to determine optimal cut-off points for triggering a colonoscopy, proposals have ranged from 45–150 ng Hb/mL. However, there remain a small subgroup of patients with levels of 10–45 ng/mL where advanced neoplasia will be missed, and for this reason, NHS England has proposed a clinical evaluation, offering CCE to individuals with FIT concentrations in the 10–99 ng Hb/mL range [ 76 , 77 , 78 ].…”
Section: The Role Of Colon Capsule Endoscopy In Screening For Advance...mentioning
confidence: 99%
“…In a previous article we showed that the ratio between the number of true-positive cases and the number of falsenegative cases was approximately 2.8 for cutoff values close to 100 ng Hb/mL. 7 This ratio is probably larger below 100 ng Hb/mL and smaller above 100 ng Hb/mL, whereas we assumed that the ratio decreases linearly going through 2.8 at 100 ng Hb/mL and 1.0 at 1000 ng Hb/mL (Fig. 1, solid line).…”
Section: Definitionsmentioning
confidence: 90%
“…Choosing the optimal cutoff value is a delicate decision requiring consideration of both benefits and harms. 7 Although it has been shown that sensitivity and specificity of the FIT varies by age and gender [8][9][10][11][12] and studies have emphasized the need for more tailored screening strategies, 8 most population-based CRC screening programs have chosen to use the same cutoff value for all participants. The aim of this study was to develop age-and gender-specific cutoff values using data from the prevalent round of the Danish FIT-based CRC screening program and to test their performance in silico.…”
mentioning
confidence: 99%